(untitled) (Madhyabindu Journal, 2025)
The main objective of this study was to identify purposes of using different social media platforms by university students studying in different faculties, i.e., management, arts and humanities, and education. A descriptive research design was employed under quantitative inquiry. A Google Form questionnaire was administered, and responses were collected purposefully from students studying at Madhyabindu Multiple Campus and Kumarwarti Multiple Campus. Out of 350 responses, only 311 complete responses were further processed and analyzed using descriptive statistical tools such as frequency, percentage, and chart. This study reveals that Facebook, YouTube, WhatsApp, and Instagram social media platforms are used by the majority of students for two or more hours each day, aiming to connect other people and share personal experience through photos, videos, and texts rather than academic and professional purposes. However, findings were drawn based on the responses of only 311 sample students, which may restrict the generalization of the findings of this study to the whole population. This paper contributes to the prevailing body of knowledge on the use of social media platforms by university students. Accordingly, this will be helpful for educational institutions, policymakers and social media platforms to make different provisions and offers regarding the social media sites.